PENGUKURAN KINERJA DENGAN ANALISIS BALANCED SCORECARD PADA PD. BPR BANK DAERAH LAMONGAN - Faishol, Ahmad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2012)
Fourth performance study result perspective balanced scorecard are learning perspectivePerformance and growth point out that firm can increase job ability fires an employee andincrease employee discipline so get to create good working condition. It is evident thatcorporate effort can increase produkvitas employee. Internal business process perspectiveperformance points out that firm can increase service to client. It is evident with decreasefoots up client complaint and getting needed time quick for client service process. But thatfirm effort cant yet back up developing to product that becomes firm pledge. Clientperspective, customer perspective performance points out that firm cant yet give customersatisfaction; it is evident with market compartment growth that constant. That performancestill lag with industry BPR performance, notably deep its credit growth this perspectiveperformance wills be cause be constrained by it propertied growth step-up. Financialperspective performance points out that firm cant yet reach propertied growth zoom andincreasing efficiency.Keywords: Balance scorecard, financial performance,non financial performance.